Incidence of lateral incisor root resorption associated with impacted maxillary canines - Lipshatz Jeff; Ptasznik Ronnie; Wenig Shmuli (Sciendo, 2021)
The aim of this study was to determine the incidence of lateral incisor root resorption associated with impacted maxillary canines and determine predisposing factors that may be used to predict its occurrence.